LEVELS OF UNDERSTANDING OF THE HISTORY CONCEPTS AT THE ENTRANCE STAGE IN THE 4TH GRADE SOCIAL STUDIES LESSON OF ELEMENTARY SCHOOL STUDENTS: THE CASE OF MANISA DEMIRCI DISTRICT - Gülşen ALTINTAŞ (Fırat University, 2019)
The aim of this study was to examine the level of understanding the history concepts at the entrance stage in the 4th grade Social Studies course of elementary school students. The study was conducted with descriptive analysis of qualitative research methods. Content analysis was used to analyze the data. A total of 31 students from four different primary schools participated in the study from the upper-middle and lower socio-economic level in the district of Manisa Demirci according to the maximum